Degenerin channel activation causes caspase‐mediated protein degradation and mitochondrial dysfunction in adult C. elegans muscle. Issue 2 (4th June 2015) - Gaffney, Christopher J.; Shephard, Freya; Chu, Jeff; Baillie, David L.; Rose, Ann; Constantin‐Teodosiu, Dumitru; Greenhaff, Paul L.; Szewczyk, Nathaniel J.
Abstract: Background: Declines in skeletal muscle structure and function are found in various clinical populations, but the intramuscular proteolytic pathways that govern declines in these individuals remain relatively poorly understood. The nematode Caenorhabditis elegans has been developed into a model for identifying and understanding these pathways. Recently, it was reported that UNC‐105/degenerin channel activation produced muscle protein degradation via an unknown mechanism. Methods: Generation of transgenic and double mutant C . elegans, RNAi, and drug treatments were utilized to assess molecular events governing protein degradation. Western blots were used to measure protein content. Cationic dyes and adenosine triphosphate (ATP) production assays were utilized to measure mitochondrial function. Results: unc‐105 gain‐of‐function mutants display aberrant muscle protein degradation and a movement defect; both are reduced in intragenic revertants and in let‐2 mutants that gate the hyperactive UNC‐105 channel. Degradation is not suppressed by interventions suppressing proteasome‐mediated, autophagy‐mediated, or calpain‐mediated degradation nor by suppressors of degenerin‐induced neurodegeneration. Protein degradation, but not the movement defect, is decreased by treatment with caspase inhibitors or RNAi against ced‐3 or ced‐4 . Adult unc‐105 muscles display a time‐dependent fragmentation of the mitochondrial reticulum that is associated with impaired mitochondrial membrane potential and that correlates with decreased rates of maximal ATP production. Reduced levels of CED‐4, which is sufficient to activate CED‐3 in vitro, are observed in unc‐105 mitochondrial isolations. Conclusions: Constitutive cationic influx into muscle appears to cause caspase degradation of cytosolic proteins as the result of mitochondrial dysfunction, which may be relevant to ageing and sarcopenia.